Social Communication for Rural Development: Lesson Learning from Creative Village - Anwar, Rully Khairul; Rizal, Edwin; Hafiar, Hanny; Sirait, Rinda Aunillah (Nyimak: Journal of Communication, 2024)
This investigation examines the development of rural communities, with a specific emphasis on participation, collaboration, and empowerment. A Creative Village (Creavill) serves as a prime example of effective, sustainable development through the implementation of economic and educational programs. The importance of community engagement in achieving comprehensive development cannot be overemphasized enough. This investigation endeavors to examine the social communication patterns amongst agriculturists and their influence on the assurance of sufficient food provisions and the enhancement of rural areas. The knowledge acquired provides important insights into strategies for enhancing resilience, especially in overcoming the challenges posed by disparities between urban and rural areas. This study focuses on the community development projects spearheaded by Creative Village, using qualitative research methodologies and case study analysis. The community’s empowerment is realized via the collaborative efforts of several sectors, including business and education. The case study of Garut Regency is an example of the success of a creative community that has effectively increased its income using new techniques. The sustained impact of empowerment requires continued commitment and cooperative participation from government agencies, communities, and outside organizations. The achievements of Creavill emphasize the importance of implementing sustainable practices. This directly supports the acceleration of comprehensive development and offers concrete solutions to economic and environmental issues faced by rural communities. This success is achieved through collaborative efforts across various complementary sectors.Keywords: Social communication, rural development, community, farmers, food securityABSTRAKPenelitian ini mengkaji proses pengembangan komunitas pedesaan, dengan fokus khusus pada konsep-konsep partisipasi, kolaborasi, dan pemberdayaan. Creavill berfungsi sebagai contoh utama pengembangan yang efektif dan berkelanjutan melalui pelaksanaan program ekonomi dan pendidikan. Pentingnya keterlibatan komunitas dalam mencapai pengembangan yang komprehensif tidak dapat ditekankan cukup. Penelitian ini berusaha memahami pola komunikasi sosial di antara petani dan bagaimana pola-pola ini mempengaruhi keamanan pangan dan kemajuan daerah pedesaan. Pengetahuan yang diperoleh memberikan wawasan penting ke dalam strategi untuk meningkatkan ketahanan, terutama dalam mengatasi tantangan yang ditimbulkan oleh disparitas antara area urban dan rural. Melalui penerapan metode penelitian kualitatif dan analisis studi kasus, investigasi berfokus pada inisiatif pengembangan komunitas yang dipimpin Creative Village. Penelitian ini mengungkapkan bahwa pemberdayaan komunitas dicapai melalui upaya bersama dari berbagai sektor, seperti bisnis dan pendidikan. Studi kasus Kabupaten Garut merupakan contoh keberhasilan komunitas kreatif yang secara efektif meningkatkan pendapatannya menggunakan teknik-teknik baru. Dampak pemberdayaan yang berkelanjutan membutuhkan komitmen dan partisipasi kerjasama yang terus menerus dari lembaga pemerintah, komunitas, dan organisasi luar. Keberhasilan Creavill menekankan pentingnya penerapan praktik berkelanjutan. Ini secara langsung mendukung percepatan pengembangan komprehensif dan menawarkan solusi konkret terhadap masalah ekonomi dan lingkungan yang dihadapi oleh komunitas pedesaan. Keberhasilan ini dicapai melalui upaya kolaboratif lintas berbagai sektor yang saling melengkapi.Kata Kunci: Komunikasi sosial, pembangunan pedesaan, masyarakat, petani, ketahanan pangan